Romania: Social Acceptance, Unmet Criteria - Bíró, Bíborka Eszter (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
The present chapter explores the most important monetary policy issues in Romania; specifically presents Romania’s state of preparedness for joining the euro area, its place and role in the banking union (as an outsider but EU Member State), and the measures it took during the crisis. This chapter also examines the different components of the Maastricht criteria, such as the price stability criterion, government budgetary position criterion, exchange rate stability criterion, and interest rate convergence criterion. A short detour is made to discuss the real convergence criteria in addition to the nominal criteria. Moreover, the most important findings referring to Romania in the Flash Eurobarometer Report are presented, providing insights into public opinion concerning the adoption of the common currency. Subsequently, aspects related to the banking union, the Single Rulebook, and banking supervision are explored. In this context, it is important to mention that Romania follows a dual supervisory mechanism, in which banking supervision requires a national authority (the National Bank of Romania) in addition to the European one. However, as Eurozone banks own a large part of the Romanian banking system, the Single Supervisory Mechanism, the domestic supervisory authority of Eurozone banks, is a key partner of the National Bank of Romania. Further, this chapter discusses the monetary aspects of crisis management processes, the most important decisions of the Governing Council of the National Bank of Romania on monetary policy issues from 2020 to 2023, why the monetary policy interest rate changed from 1.25%/year at the beginning of 2021 to 7% at the beginning of 2023 (where it remained until October 2023), and changes in the inflation rate. Keywords: nominal convergence, real convergence, banking union, euro adoption, monetary policy interest rate, inflation rate